Analyse climatique de la région de Gouré, Niger oriental : récentes modifications et impacts environnementaux - Pierre Ozer; Catherine Bodart; Bernard Tychon (Cybergeo, 2005)
Since the late 1960s, the Sahel is affected by a dramatic drought. This article analyses climatic variations recorded in the Gouré area, eastern Niger, between 1936 and 2003. It appears that the drought ended in the late 1980s. However, the rainfall increase did not lead to an extension of the length of the rainy season. The study of the wind shows that correct data was recorded during the two first years of the station of Gouré (1984 and 1985). Afterwards, wind speed was entached by errors and was not properly reported until 1997. The situation is alarming as we know that neighboring stations meet the same problems and that no synoptic station currently reports wind values in eastern Niger. However, based on wind speed and deflation data recorded in 1984, a threshold wind speed of 7 m/s was determined in Gouré. Finally, from measurements of horizontal visibility reduced by mineral dust, our results suggest that air quality is reduced because of the high frequency of wind erosion. The confrontation of our results with recent environmental studies in that region show that the end of the drought did not lead to any landscape improvement. Increasing human pressure tends to be the main driving factor of land degradation.